Społeczność łódzkich esperantystów w latach Wielkiej Wojny - Stawiszyńska, Aneta (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2014)
The outbreak of World War I temporarily stopped the process „Lodz Esperanto Societo”. Organization reactivated after a few months and stood intensive activities aimed at promoting the artificial language created by Ludwig Zamenhoff in society of Lodz. The most important activities were Esperanto Evenings, which were voiced during lectures devoted to the artificial language and also presented the associated artistic programs. An important element of this activity were numerous press reports of the benefits of the knowledge of that language. During the war, also organized a number of language courses at different levels. In Lodz also functioned library offering positions in Esperanto. Lodz Esperanto speakers regularly published their articles in the press. Among the most discussed period in Lodz Esperanto should mention figures such as Vladimir Pfeiffer, Heinrich Zimmermann and Franz Ender.